2021
DOI: 10.1002/saj2.20271
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural peatlands conservation: How does the addition of plant biomass and copper affect soil fertility?

Abstract: Subsidence, erosion, and degradation in agricultural peatlands are leading to the disappearance of highly fertile farmland. This study investigated two strategies aimed at extending the lifespan of cultivated peat soils: the application of straw and wood chips to compensate for soil losses and the application of copper (Cu) to slow peat decomposition, based on previous recommendations. Peat soil samples (270 g) were amended with 11 t ha -1 of biomass materials (14.8 g kg -1 ) and 235.6 mg Cu kg -1 and incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
1
3
0
1
Order By: Relevance
“…The immobilization of soil mineral N following incorporation of willow chip corroborates previous findings (Holtz et al 2004;Gebhardt et al 2017;Espinosa et al 2020;Bourdon et al 2021;Dessureault-Rompré et al 2022;Marmier et al 2022). This N immobilization implies that willow chip addition can potentially mitigate nitrate availability for leaching, especially after potato harvest when high residual nitrate coexists with excessive moisture (Homyak et al 2008;Moorman et al 2010;Li et al 2013;Marmier et al 2022).…”
Section: Effect Of Willow Chip Application On Nitrogen Cyclingsupporting
confidence: 86%
See 1 more Smart Citation
“…The immobilization of soil mineral N following incorporation of willow chip corroborates previous findings (Holtz et al 2004;Gebhardt et al 2017;Espinosa et al 2020;Bourdon et al 2021;Dessureault-Rompré et al 2022;Marmier et al 2022). This N immobilization implies that willow chip addition can potentially mitigate nitrate availability for leaching, especially after potato harvest when high residual nitrate coexists with excessive moisture (Homyak et al 2008;Moorman et al 2010;Li et al 2013;Marmier et al 2022).…”
Section: Effect Of Willow Chip Application On Nitrogen Cyclingsupporting
confidence: 86%
“…The impact of wood chips on soil N immobilization is inconsistent in the literature. Some studies observed N immobilization following wood chip applications (Mackensen et al 2003;Holtz et al 2004;Gebhardt et al 2017;Espinosa et al 2020;Bourdon et al 2021;Dessureault-Rompré et al 2022;Marmier et al 2022). Others found no N immobilization (Burgess et al 2002;Tahboub et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, irreversible carbon losses in organic soils have been compensated in part by biomass additions [45][46][47][48] that must also alter the C:N:P stoichiometry in the soil. Soil and fertilizer N and P would thus impact not only the N and P cycles but also trigger soil carbon loss.…”
Section: Nitrogenmentioning
confidence: 99%
“…Tanah gambut terutama yang berada di daerah tropis memiliki sifat fisika, kimia dan biologi tertentu yang mencerminkan ciri khas dari tanah tersebut. Sifat-sifat yang menjadi ciri khas tersebut adalah pH relatif rendah antara 3-5 (Hikmatullah dan Sukarman, 2014), ketersediaan nutrisi terbatas (Bourdon et al, 2021), penurunan permukaan gambut, bahan penyusun yang berasal dari kayu-kayuan, suhu lingkungan berkisar antara 25-32 o C (subsidence) (Ikkala et al, 2021). Selain itu, sifat lain yang juga dimiliki adalah kandungan organik yang tinggi karena dalam pembentukannya terdapat tanaman air dan vegetasi lahan basah yang mati dan melapuk secara bertahap membentuk lapisan dan terperangkap selama beberapa waktu (Falatehan dan Sari, 2020).…”
Section: Pendahuluanunclassified